The fishery of Danau Sentarum - Dudley, R.G. (2000)
Management of the Danau Sentarum National Park for ecosystem and species conservation must accomodate fishing activity by thousands of villagers living there. Fishery investigations helped determine how this might be accomplished. Fishing gear surveys revealed that villagers use 800 km of gill nets, 20,000 traps and 500,000 hooks in 80,000 ha of lakes, rivers and flooded forest within the park. Data from 4,000 catches were collected by local people during 1992 through 1995.The estimated annual catch of between 7,800 and13,000 tonnes (or 97,5 to 162,5 kg ha-l) is caught by cylindrical rattan traps 23%, gillnets 20%, cast nets 18%, other traps 15%, hooks 14% and funnel nets 9%. These data provide insight into what changes might make fishing activity more compatible with conservation. Villagers and data indicate some species are less abundant and smaller than in the previous years, but the needed management via direct government regulation is unlikely to succeed. A promising approach would emphasize management by villagers. Regulations at the village level exist, as does understanding of the need for a better management system. Developing this potential into an officially recognised fishery management system could improve conservation of this important wetland. Suggested management starting points include the concept of trading exlusive resource use rights for compliance with conservation regulation and the establishment of a residence permit system for the park. Suggestions for mesh size regulations and other gear changes, to be used as starting points for discussions with villagers are also presented.